2018
DOI: 10.1371/journal.pone.0205058
|View full text |Cite
|
Sign up to set email alerts
|

Human and entomologic investigations of chikungunya outbreak in Mandera, Northeastern Kenya, 2016

Abstract: Chikungunya is a reemerging vector borne pathogen associated with severe morbidity in affected populations. Lamu, along the Kenyan coast was affected by a major chikungunya outbreak in 2004. Twelve years later, we report on entomologic investigations and laboratory confirmed chikungunya cases in northeastern Kenya. Patient blood samples were received at the Kenya Medical Research Institute (KEMRI) viral hemorrhagic fever laboratory and the immunoglobulin M enzyme linked immunosorbent assay (IgM ELISA) was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 38 publications
1
23
0
Order By: Relevance
“…reservoirs for CHIKV and for many other arboviruses. The proximity of the present study area to Kenya, a country reported the occurrence of CHIKV infection [14][15][16]20] could have resulted in an increased sero-prevalence of CHIK in the present study area since migration and travel of people across the border inferring the likelihood of transmission of this virus.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 93%
See 1 more Smart Citation
“…reservoirs for CHIKV and for many other arboviruses. The proximity of the present study area to Kenya, a country reported the occurrence of CHIKV infection [14][15][16]20] could have resulted in an increased sero-prevalence of CHIK in the present study area since migration and travel of people across the border inferring the likelihood of transmission of this virus.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 93%
“…CHIK outbreaks have been reported from many African countries including Uganda [13], Kenya [14][15][16], Sudan [17] and Tanzania [18]. Despite the proximity of Ethiopia to these countries, and migration of people across the border between Ethiopia and contingent countries as well as the existence of the potential mosquito vectors (Aedes bromeliae and Aedes aegypti) responsible for transmitting CHIKV in the study area [9], and the repeatedly occurrence of CHIK outbreaks in Kenya [14-16, 19, 20], either health facility or community-based survey of CHIKV infection has not been conducted in the present study area.…”
Section: Introductionmentioning
confidence: 99%
“…This activity needs unrelenting contribution from the whole of affected communities (4,24). High numbers of disposable water containers has been shown to be a risk in other chikungunya outbreaks in another countries and in Indonesia as well, as it increases breeding sites for Aedes (6,12,16,25,(29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…The legend shows the country names and their year of accession into the EAC in bracket. Non-human primates, humans [115,149,192,[195][196][197][200][201][202] Ndumu During this time there were more than 20 known arboviruses including the Yellow fever virus which were unrelated to the virus, hence it was named Bunyamwera [30,31]. The virus has spread across many regions over the past decades and remains an important virus due to its ability to cause human diseases.…”
Section: Bunyaviridaementioning
confidence: 99%
“…taylori and Ae. cordellieri in South Africa and non-human primates [192,201,202]. Outbreaks of CHIKV have occurred across the globe [1] since the first outbreak in Tanzania.…”
Section: Chikungunya Virus (Chikv)mentioning
confidence: 99%